Single-Molecule Real-Time and Illumina Sequencing to Analyze Transcriptional Regulation of Flavonoid Synthesis in Blueberry - Tang, Qi; Chi, Fu-Mei; Liu, Hong-Di; Zhang, Hong-Jun; Song, Yang (Frontiers in Plant Science, 2021)
Blueberries (Vaccinium corymbosum) contain large amounts of flavonoids, which play important roles in the plant’s ability to resist stress and can also have beneficial effects on human health when the fruits are eaten. However, the molecular mechanisms that regulate flavonoid synthesis in blueberries are still unclear. In this study, we combined two different transcriptome sequencing platforms, single-molecule real-time (SMRT) and Illumina sequencing, to elucidate the flavonoid synthetic pathways in blueberries. We analyzed transcript quantity, length, and the number of annotated genes. We mined genes associated with flavonoid synthesis (such as anthocyanins, flavonols, and proanthocyanidins) and employed fluorescence quantitative PCR to analyze the expression of these genes and their correlation with flavonoid synthesis. We discovered one R2R3 MYB transcription factor from the sequencing library, VcMYB1, that can positively regulate anthocyanin synthesis in blueberries. VcMYB1 is mainly expressed in colored (mature) fruits. Experiments showed that overexpression and transient expression of VcMYB1 promoted anthocyanin synthesis in Arabidopsis, tobacco (Nicotiana benthamiana) plants and green blueberry fruits. Yeast one-hybrid (Y1H) assay, electrophoretic mobility shift assay, and transient expression experiments showed that VcMYB1 binds to the MYB binding site on the promoter of the structural gene for anthocyanin synthesis, VcMYB1 to positively regulate the transcription of VcDFR, thereby promoting anthocyanin synthesis. We also performed an in-depth investigation of transcriptional regulation of anthocyanin synthesis. This study provides background information and data for studying the synthetic pathways of flavonoids and other secondary metabolites in blueberries.